Development Strategy of Integrated Salaf Curriculum in Madrasah Aliyah to Improve the Graduates’ Quality in Rasyidiyah Khalidiyah Amuntai Islamic Boarding School - Fadillah, Haris; Trisnamansyah, Sutaryat; Insan, Husen Saeful; Sauri, Supyan (Journal of Education Research and Evaluation, 2021)
Curriculum is an instrument used to achieve educational objectives effectively and efficiently. Curriculum functions to make the learning process run well; thus, the educational objectives can be adequately reached. In fact, the curriculum is dynamic where it can flexibly follow technological development. This research aims to investigate: (1) Plan of the management the Salaf curriculum integrated with Madrasah Aliyah (Islamic Senior High School) curriculum to improve the graduates’ quality; (2) Organizing of management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality; (3) the implementation of the management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality; (4) Evaluation of the management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality; (5) Problems of the management of Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality; and (6) Efforts to overcome the problems of the management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality. This research employed descriptive qualitative with a case study in Rasyidiyah Khalidayah Amuntai Islamic Boarding School in South Kalimantan. Eventually, the research results identified that (1) the management of the Salaf curriculum integrated Madrasah Aliyah curriculum to improve the graduates’ quality was planned correctly; (2) the organizing of management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality was implemented by concerning the integrated subjects; (3) the management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality was conducted through curricular activities and extracurricular activities; (4) the management of Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality was evaluated collectively and formatively; (5) the problems found in the management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality was the excessive subjects taught; and (6) the efforts done to overcome the management of the Salaf curriculum integrated with Madrasah Aliyah curriculum to improve the graduates’ quality were strengthening Salaf learning, such as yellow book, tahfidz Al Qur’an and empowering strategist school resources.